2008
DOI: 10.1007/s10509-008-9965-6
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter in space: from star dust to the Solar System

Abstract: Organic compounds of high degree of complexity are now known to be widespread in the Universe, ranging from objects in our Solar System to distant galaxies. Through the techniques of millimeter-wave spectroscopy, over 140 molecules have been identified through their rotational transitions. Space infrared spectroscopy has detected the stretching and bending modes of compounds with aromatic and aliphatic structures. Analyses of samples of meteorites, comets, asteroids, and interplanetary dust also revealed a ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 110 publications
2
35
0
Order By: Relevance
“…Such a systematic study of the gasphase molecules presents an important step to understand the synthesis of more complex aromatic and aliphatic compounds in evolved stars, and their role in the distribution of organic compounds throughout the Galaxy (Kwok 2009). A detailed study of chemical processes in different physical conditions and evolutionary stages will be reported in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Such a systematic study of the gasphase molecules presents an important step to understand the synthesis of more complex aromatic and aliphatic compounds in evolved stars, and their role in the distribution of organic compounds throughout the Galaxy (Kwok 2009). A detailed study of chemical processes in different physical conditions and evolutionary stages will be reported in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In corroboration, it has been found that cosmic regions of high organic molecular densities are often associated with regions of stellar formation (Ehrenfreund and Charnley, 2000). Over 140 organic molecules have now been found in space, although the nucleobases have yet to be detected (Kwok, 2009). The dispersed organic molecules are then suggested to have been deposited into the Earth's oceans through the vehicle of colliding comets, asteroids, or space dust.…”
Section: Ambient Conditions Of Insipient Lifementioning
confidence: 92%
“…Complex organic molecules are, in fact, ubiquitous throughout the cosmos and are formed basically by the action of UV light on simpler prebiotic organic and inorganic carbon compounds (Callahan et al, 2011;Kwok, 2009;Gerakines et al, 2004). Many species of organic molecules (especially those with conjugated systems -Zollinger, 2003) when dissolved in water are very efficient absorbers and dissipaters of UV and visible photons and should therefore be considered as organic pigments during the Hadean and Archean eons.…”
Section: World Of Earliest Pigments (Hadean Eonmentioning
confidence: 99%